2021
DOI: 10.1007/s10140-021-01905-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pneumonia—ultrasound, radiographic, and computed tomography findings: a comprehensive pictorial essay

Abstract: Ultrasound, chest X-ray, and computed tomography (CT) have been used with excellent results in diagnosis, first assessment, and follow-up of COVID-19 confirmed and suspected patients. Ultrasound and chest X-ray have the advantages of the wide availability and acquisition at the patient's bed; CT showed high sensitivity in COVID-19 diagnosis. Ground-glass opacities and consolidation are the main CT and X-ray features; the distribution of lung abnormalities is typically bilateral and peripheral. Less typical fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…A traditional division of lung lesions, according to its anatomical location in one of the five lung lobes, was found to be useful for predicting patient outcomes at the time of presenting to the emergency department 30 . However, the MBrixia score allows for quantification of the overall lesion burden, and it is advantageous in COVID-19 pneumonia, since studies using higher-resolution imaging, such as CT imaging, have reported COVID-19 lesions in lobar segments—as opposed to entire lung lobes 31 , 32 . Furthermore, when comparing the Brixia score with the MBrixia score, as shown in Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A traditional division of lung lesions, according to its anatomical location in one of the five lung lobes, was found to be useful for predicting patient outcomes at the time of presenting to the emergency department 30 . However, the MBrixia score allows for quantification of the overall lesion burden, and it is advantageous in COVID-19 pneumonia, since studies using higher-resolution imaging, such as CT imaging, have reported COVID-19 lesions in lobar segments—as opposed to entire lung lobes 31 , 32 . Furthermore, when comparing the Brixia score with the MBrixia score, as shown in Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Increased bronchovascular markings indicate thickening of the bronchial wall due to inflammation that damages the bronchial wall and is relatively uncommon in COVID-19 patients. 16 The findings on air bronchograms in previous studies were diverse. According to a literature review by Lamoro et al (2020), air bronchogram was found with a highly variable frequency in various studies, ranging from 8% to 80% of study subjects.…”
Section: Chest X-ray Characteristicsmentioning
confidence: 99%
“…Sometimes the test results may not be available immediately and may cause a false negative result, due to the quality of the sample [ 31 ]. In such situations, various chest imaging modalities such as X-ray, CT, and Ultrasound (US) help to confirm COVID-19 suspects [ 32 ]. The combination of AI techniques with various imaging modalities can assist to increase the efficiency of COVID-19 detection worldwide [ 32 ].…”
Section: Ai Techniques For Covid-19 Detectionmentioning
confidence: 99%
“…In such situations, various chest imaging modalities such as X-ray, CT, and Ultrasound (US) help to confirm COVID-19 suspects [ 32 ]. The combination of AI techniques with various imaging modalities can assist to increase the efficiency of COVID-19 detection worldwide [ 32 ].…”
Section: Ai Techniques For Covid-19 Detectionmentioning
confidence: 99%